The Effect Of Security And Trust On Mobile Banking Customer Satisfaction Mediated By Convenience Factors - Wulan Suci, Fimi Catur; Dahlan, Kandi Sofia Senastri (Al-Makki Publisher, 2023)
The purpose of this study is to analyze mobile banking customer satisfaction influenced by security and trust mediated by convenience factors for Livin' by Mandiri users at the Tangerang Ahmad Yani branch. This study used a quantitative approach. The survey was conducted to 242 Livin' by Mandiri users at the Ahmad Yani Tangerang Branch. This study uses Partial Least Squares SEM or so-called PLS-SEM and identifies the relationship between variables and conceptual and operational definitions using previous research, which includes using security and trust variables as independent variables, customer satisfaction as dependent variables, and convenience factors as mediation variables. The results of this study show that Security has a positive and significant effect on the Convenience Factor, Trust has a positive and significant effect on the Convenience Factor, the Convenience Factor has a positive and significant effect on Customer Satisfaction, Security has a positive and significant effect on Customer Satisfaction, Trust has an effect but not significant on Customer Satisfaction, the Convenience Factor has a positive and significant effect mediating Security on Customer Satisfaction, and Convenience Factors have a positive and significant effect on mediating Trust in Customer Satisfaction. This research is limited to only examining the variables of security, trust, convenience factors, and customer satisfaction and only to Bank Mandiri customers, especially Livin' by Mandiri users at the Tangerang Ahmad Yani branch.